2011
DOI: 10.1021/jp203944c
|View full text |Cite
|
Sign up to set email alerts
|

Nature of the Polycarbonyl Species on Ru/ZrO2: Reassignment of Some Carbonyl Bands

Abstract: The carbonyls formed after CO adsorption on Ru/ZrO 2 are strongly affected by the sample pretreatment. A procedure leading to reproducible results is activation of the sample at 673 K first in oxygen and then in vacuo followed by adsorption of CO at 373 K. After this treatment three main bands are formed in the carbonyl region at ca. 2130, 2070, and 2000 cm À1 . These bands correspond to two kinds of cationic polycarbonyls: (i) species characterized by set of bands at 2130 cm À1 and in the 2100À2030 cm À1 regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 65 publications
3
14
0
Order By: Relevance
“…It should be noted, however, that the CO IR spectra recorded at liquid N 2 of a sample exposed to air for prolonged time are virtually identical to those carefully manipulated under protective atmosphere (data not shown), indicative of the stability of the material to oxidation or chemical change at ambient conditions. The spectral features at 2194 and 2174 cm −1 , which grow at higher CO pressures, are assigned to CO on ZrO 2 , in line with the literature . The redshifted features detected at 2121, 2061, and 2023 cm −1 are assigned to one or two CO molecules adsorbed on cationic, single‐atom Ru sites.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…It should be noted, however, that the CO IR spectra recorded at liquid N 2 of a sample exposed to air for prolonged time are virtually identical to those carefully manipulated under protective atmosphere (data not shown), indicative of the stability of the material to oxidation or chemical change at ambient conditions. The spectral features at 2194 and 2174 cm −1 , which grow at higher CO pressures, are assigned to CO on ZrO 2 , in line with the literature . The redshifted features detected at 2121, 2061, and 2023 cm −1 are assigned to one or two CO molecules adsorbed on cationic, single‐atom Ru sites.…”
Section: Resultssupporting
confidence: 88%
“…Under high vacuum (10 −6 mbar) at 85 K, the band centered at 2174 cm −1 , attributed to Zr 4+ ‐CO species, decreased in intensity and blueshifted to 2183 cm −1 , although no change was observed in the Ru‐CO region. The band located at 2183 cm −1 , thought to involve more electrophilic Zr 4+ species, only fully disappeared at 273 K. In the Ru‐carbonyl region, the bands 2120 and 2023 cm −1 decreased gradually upon heating and vanished completely at 523 K. Similarly, Mihaylov and co‐workers also noted the disappearance of a band at approximately 2130 cm −1 upon heating to 473 K . Upon increasing the temperature, the lower wavenumber band showed some additional structural complexity, with bands centered at 2055 and 1976 cm −1 starting to develop from 473 K, and being stable up to 673 K. Relatedly, for a Ru/TiO 2 system, bands assigned to Ru 3+ (CO) 2 or Ru 2+ (CO) 3 species (observed at 2151–2132 and 2090–2070 cm −1 ) could be removed by evacuation at 473 K, whereas bands associated with Ru 2+ (CO) 2 complexes, located at lower frequencies (2101–2080 and 2038–2023 cm −1 ) remained up to 573 K .…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…The reaction proceeded on a silver-loaded zeolite and did not occur (at ambient temperature) on several other catalysts, e.g. Cu-ZSM-5, 4 Cu/MCM-41, 5 Fe-ZSM-5 and Fe-BEA, 6 Ni-ZSM-5 and Ni/SiO 2 , 7 Ru/ZrO 2 , 8 Pt/SiO 2 9 and Pt-Cu/SiO 2 . 10 Moreover, we found that an optimal reduction degree of the sample was needed for the reaction.…”
Section: Introductionmentioning
confidence: 97%
“…The formation of a metal-carbonyl complex was observed during carbonization in the temperature range of 200-500 °C. However, the results obtained from the spectra of C=O were much more complicated because of the presence of several different C=O species on different types of reduced and partially oxidized Ru sites, which made the interpretation of the observed spectra more difficult than with other metals [39][40][41]. Fig.…”
Section: Discussionmentioning
confidence: 99%